Cells at Work: Media Integration Mapping - Hedi Amelia Bella Cintya; Alvanov Zpalanzani Mansoor; Hafiz Aziz Ahmad (Universitas Multimedia Nusantara, 2021)
Cells at Work is a Japanese comic by Shimizu Akane that tells about body cells’ science. The comic gains popularity as edutainment and adapted into several educative media such as spin-offs comics, picture books, games, stage plays, and many more. While it can act as good alternatives to learn about the science of cells, adaptation to media that is too diverse can create ambiguity, confusing its users. The purpose of this research is to create a media integration mapping of Cells at Work. This research employs a qualitative descriptive method. The descriptive method is used to describe and determine the use of each adaptation medium. Then this research will map the media integration. The findings show that the diversity of educational media has its roles and purposes. Spin-off comics have specific topics that can broaden the user's knowledge of various cells. At the same time, picture books are aimed at readers who want to study cells in depth without any side stories. Games are aimed at people who prefer interactive learning. The findings from this study can be used as a consideration for creating and integrating educational media. Keywords: media integration; mapping; educational comic; science; cells at work.